Repair of multiple abdominopelvic aneurysms: is the open approachstill valid? A case report - Cubas, W. Samir (2024)
Multiple Aneurysmal Arterial Disease (MAD) is an extremely rare arterial vascular condition and is produced by an abnormal alteration of smooth muscle cells and neutrophils, producing a multiple-aneurysmal degeneration. We present the case of a 36-year-old patient with a MAD in the cerebral territory and extremities with no surgical indication; however, with an aneurysm of the right inferior renal segmental artery, inferior mesenteric artery, left common iliac artery, and right internal iliac artery with surgical indication. An open approach with single-stage surgical repair, including graft interposition, bypass, exclusion, and vascular reimplantation, was performed. The surgical and postoperative course was uneventful, and the patient was discharged with an indication for outpatient follow-up. The open approach may be the best option for young patients with MAD, especially in the abdominopelvic region, without the need for high resources, with satisfactory results and improved patient survival.